Martin Van Buren : America's first politician - Bradley, James M. (Oxford University Press, 2024)
In early June 1824, Martin Van Buren, New York's junior United States senator, went to Virginia to meet Thomas Jefferson, a man "whose character, conduct and principles formed my beau ideal of thorough patriotism and accomplished statesmanship," Van Buren would one day write. Eighty-one, ailing, and chased by creditors, the former president never refused guests, even though the frequent entertaining added to his money woes. An air of mystery surrounded the visit. In Washington, word spread that Van Buren was heading South, but only a handful of people knew what lay behind his trip. It was a presidential election year, and several high-profile politicians were seeking the office. One of them was the US Treasury secretary, William H. Crawford. Van Buren was backing Crawford, whose campaign was in serious trouble. An official benediction from Jefferson, patriarch of the Republican Party, could turn Crawford's fortunes around. But people did not ask ex-presidents for endorsements then, and ex-presidents were not supposed to give them. Van Buren had little use for such niceties, though he recognized that a trip to Monticello might be viewed unfavorably and wanted it kept quiet. "Mention this to no one except Mr Crawford," he wrote in a letter to Asbury Dickins, a Treasury clerk and Crawford aide"- Provided by publisher.